Analysis of risk factors and short-term prognostic factors of arrhythmia in patients infected with mild/moderate SARS-CoV-2 Omicron variant - Yan, Lijie; Wu, Jintao; Fan, Xianwei; Liu, Jingjing; Zhang, Leiming; Hu, Juan; Li, Xuejie; Su, Yandong; Zhang, Futao; Xu, Xizheng; Chen, Xiaosheng; Yang, Haitao (Frontiers in Medicine, 2023)
Objectives: To investigate the risk factors of arrhythmia in patients infected with the SARS-CoV-2 Omicron variant and the factors influencing prognosis. Methods: Data from 192 Omicron infected patients with arrhythmia (AH group) and 100 Omicron infected patients without arrhythmia (Control group) were collected. Patients in the AH group were divided into the good and poor prognosis groups, according to the follow-up results 4-6 weeks after infection. The general and clinical data between the AH and Control groups, and between the good and poor prognosis groups were compared. The variables with differences between the groups were included in the multivariate logistic regression analysis, and the quantitative variables were analyzed by receiver operating characteristic curve to obtain their cut-off values. Results: Compared with the control group, the body mass index (BMI), proportion of history of arrhythmia, proportion of antibiotics taken, heart rate, moderate disease severity, WBC, and the AST, creatine kinase (CK), CK isoenzyme (CK-MB), myoglobin (Mb), high-sensitive troponin Ⅰ (hs-cTnⅠ), lymphocyte ratio and hs-CRP levels in the AH group were significantly higher (P<0.05). In addition, obesity (BMI ≥24 kg/m2), fast heart rate (≥100 times/min), moderate disease severity, and WBC, CK-MB and hs-cTnⅠ levels were independent risk factors of arrhythmia for patients with Omicron infection (P<0.05), and hs-CRP was a protective factor (P<0.05). Compared with the good prognosis group, the age, proportion of history of arrhythmia, heart rate, proportion of moderate disease severity, and hs-CRP, CK, Mb and hs-cTnI levels were significantly higher in the poor prognosis group, while the proportion of vaccination was lower in the poor prognosis group (P<0.05). Advanced age (≥65 years old), proportion of history of arrhythmia, moderate disease severity, and hs-CRP, Mb and cTnⅠ levels were independent risk factors for poor prognosis of patients with arrhythmia (P<0.05), while vaccination was a prognostic protective factor (P<0.05). Conclusions: The factors that affect arrhythmia and the prognosis of patients infected with Omicron include obesity, advanced age, medical history, fast heart rate, severity of the disease, WBC, hs-CRP, and myocardial injury indexes, which could be used to evaluate and prevent arrhythmia complications in patients in the future.